Opinion analysis regarding the use of digital tools by merchants in the municipality of Tefé-AM (Research, Society and Development, 2022)
The world has been undergoing several digital transformations, and the application of new technologies for the creation of social currencies and financial platforms is something that has been spreading among the low-income population, due to the popularization of the Internet, because it is a more profitable exit and safer, avoiding the accumulation of money in physical form. With the creation of new technologies, the imposition of standards for smartphone users is growing, more and more companies are developing applications with their usage format. However, factors such as geographic diversity becomes a major challenge in the process of popularizing the use of network technologies in the state of Amazonas, since many places are difficult to access. Thus, the objective of this work was to conduct an opinion survey of traders in the municipality of Tefé -Am on the use of internet, payment method used by the population, in addition to knowledge and adhering related to the use of a social currency and digital electronic platforms for this purpose. The methodology used was an interview conducted in person in 12 categories of trades divided into 19 neighborhoods. The collected data were entered in the Google Forms database and later performed analysis through tables and graphs. At the end of the research it was found that the use of applications for financial transactions is still low, but there is positive influence that the technology of a financial platform will provide in traders of the municipality of Tefé.